Is there a link between vitamin D status, SARS‐CoV‐2 infection risk and COVID‐19 severity?. (2nd November 2020) - Ferrari, Davide; Locatelli, Massimo; Briguglio, Matteo; Lombardi, Giovanni
Abstract : The outbreak of COVID‐19 emerged in December 2019 rapidly spread across the globe and has become pandemic. Little is known about the protective factors of this infection, which is equally distributed between genders and different ages while severe and poor prognosis cases are strongly associated to old males and the presence of comorbidities. Thus, preventive measures aiming at reducing the number of infection and/or their severity are strongly needed. Vitamin D has got great attention and has been claimed as potentially protective against the infection since it may be associated with immunocompetence, inflammation, aging, and those diseases involved in determining the outcomes of COVID‐19. This narrative review aims at collecting the literature available on the involvement of the vitamin D status in the pathogenesis of COVID‐19 and the putative utility of vitamin D supplementation in the therapeutics. It emerges that a poor vitamin D status seems to associate with an increased risk of infection whereas age, gender and comorbidities seem to play a more important role in COVID‐19 severity and mortality. While randomized control trials are needed to better inquire into this topic, vitamin D supplementation may be useful beside its potential effects on SARS‐CoV‐2 infection and COVID‐19.